Power and weakness - Kagan, Robert (2002)
Robert Kagan offers his views on the differences between Europe and the United States and offers solutions to the growing divide in the Atlantic alliance. In summary, much of Kagan's narrative is persuasive; however, his conclusions and recommendations are wearily inadequate for an 11,000 word essay.